(untitled) (Medico Legal Update, 2021)
Hypertension is a high-risk condition that causes of deaths, stroke, and coronary heart disease. This study aims to determinethe effect of giving pigeon pea (Cajanus cajan) baruasa on systolic and diastolic blood pressure of elderly with hypertension. The research is quasy experimental design with pre-post test group. A total of 36 elderly people with hypertension were divided into intervention group and control group by random sampling. Data were analyzed using Mann-Whitney and Wilcoxon with 95% confidence level. The results of this study indicate that: There is an effect giving pigeon pea (Cajanus cajan) baruasa on the systolic blood pressure of elderly with hypertension (p = 0.001 <0.05); (4) There is an effect giving pigeon pea (Cajanus cajan) baruasa to the diastolic blood pressure of elderly with hypertension (p = 0.001 <0.05). The conclusion of this study that consumption of pigeon pea (Cajanus cajan) baruasa can reduce of blood pressure on elderly hypertensive in Jeneponto district. The suggestions for researcher presumably can further investigate the influence of pigeon pea baruasa on blood pressure in elderly man with hypertension and long storage time (expiration date) of pigeon pea baurasa